HUBUNGAN KARAKTERISTIK PASIEN DAN PENGETAHUAN DENGAN KEPATUHAN MINUM OBAT ANTIHIPERTENSI: STUDI CROSS-SECTIONAL DI KLINIK PRATAMA - Andi Ahsan Yusma; Imran Firman (Institut Sains dan Teknologi Al-Kamal, 2026)
Hypertension is a chronic disease that requires long-term therapy; therefore, medication adherence is a key determinant of successful blood pressure control and may be influenced by patient characteristics and knowledge. This analytic observational cross-sectional study was conducted at a primary clinic in Makassar from May to July 2025 among 110 hypertensive outpatients (population: 152) selected using purposive sampling. Data were collected using questionnaires on patient characteristics, knowledge (10-item Guttman scale), and medication adherence (10-item modified ARMS-based 3-point scale); all items were valid (r-count > 0.30) and reliable (Cronbach’s alpha: knowledge 0.729; adherence 0.755). Most respondents were aged 46–55 years (39.1%), male (62.7%), had primary–secondary education (SD–SMA) (80.9%), and were employed (71.8%); high knowledge was found in 73.6% of respondents and high adherence in 79.1%. Knowledge level was significantly associated with medication adherence (p=0.002), and age (p=0.002), sex (p=0.001), education (p=0.001), and employment status (p=0.002) were also significantly associated with adherence, indicating the need for structured education and patient-tailored interventions to improve adherence and support successful antihypertensive therapy outcomes.